SAT0666 Inflamation beyond clinical remission: ultrasound as a tool to guide us to remission. (12th June 2018) - Estrada, P.; Diaz-Torné, C.; Torrente, V.; Moya, P.; Moragues, C.; De La Fuente, D.; Ros, S.; Ramirez, J.; Moreno, M.; García, E.; Puyol, M.; Busquets, N.; et al.
Abstract : Background: Among patients with RA in remission, subclinical synovitis (SS) has a prevalence of 45% and is associated with an increased risk of clinical relapse and progression to structural damage. US is a sensitive and accessible tool for evaluating SS 1, 2, 3 . Objectives: To analyse US as a tool for evaluating SS in RA patients treated with tocilizumab (TCZ), in order to assess remission, and from there on propose therapeutic tapering. Methods: Multicenter, 1 year follow up study in 45 patients with RA treated with TCZ. The project was aproved by Ethics Committees and all the patients gave their informed consent. At each visit: DAS28, SDAI, CDAI, mHAQ, US grey scale (GS) and Power Doppler (PD) parameters for 32 joints (J) and 28 tendons (T), with a semiquantitative scale from 0–3 points. A quantitative index was obtained for J and T in GS and PD and overall (EG +PD) for each patient/visit. SS was considered as the presence of synovitis with PD(+)≥2. Our intra and interobserver kappa index was 0.8. Results: A significant reduction of all clinical indexes and US variables was observed in all patients. Patients were divided into two groups: remission (R) and no remission (NR) according to whether they achieved DAS28 ≤2.6 at 12 months. Group R achieved DAS28 ≤2.6 after mo 3, whereas US showed SS (GS+, PD >2) until mo 12. The final overall PD value in the R group was 0.6 (±0.9). Conclusions: A significant number of patients achieve clinical remission within a few months of starting TCZ. The R group, achieved a good EULAR response since mo 3; a progressive improvement in PD, persisted until mo 12. We consider that these findings refer to SS. From our data we consider that dose tapering should not be initiated until at least 9 months from the start of remission. References: [1] doi 10.1002/art.22190 [2] PMID 27050636 [3] doi 10.1093/rheumatology/kex084 Disclosure of Interest: None declared